Belarus – Germany: main trends and stages of the development of intergovernmental relations in the 1990s – first half of the 2010s - Rusakovich, Andrei V. (Journal of the Belarusian State University. International Relations, 2018)
The present paper analyzes the intergovernmental relations of Belarus and Germany in the 1990s – 1st half of the 2010s, characterizes their main stages, considers the achievements and problems of interaction, and defines the place of the German vector in Belarus’s foreign-policy strategy. The author draws the conclusion that in the period under investigation Germany was Belarus’s chief political and economic partner among the developed countries and that a significant amount of prog- ress was achieved in different areas of cooperation. The difficulties in the countries’ intergovernmental relations reflected the contradictions of the functioning of the modern global system and resulted from different historical and civilizational trajectories and levels of political, economic, and cultural development.
Keywords: foreign policy; economic cooperation; political dialogue; Nazi victim compensation; humanitarian cooperation; investments; external trade; Belarus – Germany relations